PVA-ECC composite material capable of reducing sub-high temperature environment damage and preparation method thereof
Patent Information
- Application Number
- CN202611424578.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-16
AI Technical Summary
现有技术尚未提出针对亚高温环境的系统性改性方案,既未对胶凝材料进行耐热优化,也未对PVA纤维进行有效的表面改性处理,难以满足PVA-ECC在亚高温环境中长期服役的性能要求
1、本发明改性浸渍液延缓了亚高温环境下纤维的热降解,实现了纳米粒子在纤维表面的均匀、高效接枝,且改性浸渍液配制方法简便、可重复性好,适合工业化生产。
Smart Images

Figure CN122916562A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of PVA-ECC composite material technology, specifically to a PVA-ECC composite material that can reduce damage in sub-high temperature environments and its preparation method. Background Technology
[0002] PVA-ECC (polyvinyl alcohol fiber reinforced cementitious composite) is a high-toughness cementitious composite material with excellent strain hardening characteristics and multi-crack cracking features. PVA fibers exhibit good compatibility with the cement matrix, significantly improving the toughness and strength of cementitious composites. Due to its excellent tensile ductility and crack control capabilities, PVA-ECC has been widely used in engineering fields such as building structural beams, bridge structures, dam structures, expansion joints, and structural repairs.
[0003] However, a significant challenge facing PVA-ECC in actual engineering service is the performance degradation caused by long-term exposure to sub-high temperature environments (150-200℃). With global warming, high temperatures are becoming more frequent in summer, with road surface temperatures exceeding 40℃ in some areas and even reaching 80℃ in others. In the metallurgical and chemical industries, workshop building structures are often exposed to high-temperature radiation environments with surface temperatures reaching 100℃; thermal power plants can operate continuously at 100℃ or 150℃; and the localized temperatures of reactor pressure vessels and containment structures in nuclear power plants can reach above 120℃, and under abnormal conditions, may even rise to 140-160℃. Furthermore, when building structures encounter fires, although the duration of high-temperature exposure is generally short, the temperature of most areas of the concrete structural components remains in the sub-high temperature range.
[0004] The aforementioned engineering application environment posed a severe challenge to the long-term durability of PVA-ECC. PVA fibers have low thermal stability, and their decomposition temperature is close to their melting point. Even before reaching the melting decomposition temperature of PVA fibers, the tensile strength of PVA fibers significantly decreases with prolonged exposure. After 9 hours at 200℃, the tensile strength of PVA fibers dropped to 191-286 MPa, only 14.4% of that at room temperature. Simultaneously, the crystallinity of PVA fibers decreased by approximately 10%, the intermolecular hydrogen bonds were severely disrupted, and the interfacial transition region between the fiber and the cement matrix gradually disappeared.
[0005] Existing technologies have conducted relatively detailed studies on the residual mechanical properties of ECC after high-temperature fires at 200-950℃, but research on the performance damage of PVA-ECC under long-term service conditions in the sub-high temperature range of 50-200℃ remains very limited. Existing technologies mainly suffer from the following shortcomings: Firstly, PVA fibers themselves lack thermal stability. As an organic polymer material, PVA fibers are extremely sensitive to temperature changes. In sub-high temperature environments, the surface oil of the fiber gradually decomposes, the fiber begins to melt from the surface, the grains become larger and coarser, and the crystal arrangement becomes scattered and irregular. The cracks appearing on the fiber surface, the destruction of the crystal structure, and the breakage of the C-C backbone between macromolecules and the reduction of hydrogen bonds make the "weak links" on the fiber chain more fragile, and the load-bearing capacity decreases significantly.
[0006] Secondly, the fiber-matrix interface undergoes adverse evolution in sub-high temperature environments. In sub-high temperature environments, PVA fibers, due to the evaporation of oil and the melting and decomposition of the fibers, tightly bond with the fly ash spherical particles in the cement matrix, causing the interface transition zone to disappear. When the fiber tensile strength is below 1000 MPa, the fiber experiences severe wear with the cement matrix during pull-out, failing to complete the pull-out process and breaking directly, thus losing its bridging function.
[0007] Third, there is a lack of systematic modification technology solutions. Existing technologies have not proposed systematic modification solutions for sub-high temperature environments. Neither the heat resistance of the cementitious materials has been optimized, nor has the PVA fiber been effectively modified, making it difficult to meet the performance requirements of PVA-ECC for long-term service in sub-high temperature environments.
[0008] Therefore, developing a PVA-ECC composite material that can effectively reduce damage and maintain excellent tensile properties in sub-high temperature environments and its preparation method has important engineering application value and practical significance. Summary of the Invention
[0009] To address the shortcomings of existing technologies, the present invention aims to provide a PVA-ECC composite material that can reduce damage in sub-high temperature environments and its preparation method.
[0010] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a PVA-ECC composite material that can reduce damage in sub-high temperature environments includes the following preparation steps: S1. By weight, mix 1000-1200 parts of modified cementitious material and 400-450 parts of quartz sand at a speed of 40-50 r / min for 2-3 minutes to obtain a preliminary mixture; S2. Mix 280-300 parts water, 6-8 parts high-efficiency water-reducing agent (powdered polycarboxylate high-efficiency water-reducing agent), 1.2-1.4 parts hydroxypropyl methylcellulose, 0.8-1.2 parts triethanolamine, and 3-5 parts defoamer (SH-E325), and stir at 800-1000 r / min for 3-5 min to obtain a mixed wet material; S3. Add the mixed wet material obtained in step S2 to the preliminary mixture in step S1 while stirring at a speed of 40-50 r / min. After the addition is complete, stir rapidly at a speed of 100-120 r / min for 3-5 minutes to obtain the secondary mixture. S4. Sprinkle 25-30 parts of modified PVA fiber evenly into the mixture of the second step in 3-4 times, with an interval of about 30-40 seconds between each time. Stir quickly for 3-5 minutes and then pour into a standard test mold. Vibrate for 30-60 seconds, cover with plastic film and let stand for 24-48 hours. Then remove the mold and cure for 24-28 days to obtain the PVA-ECC composite material. The preparation of modified cementitious materials includes the following steps: S11. By weight, mix 15-25 parts of nano silica, 0.5-1 parts of polycarboxylate-based high-efficiency water-reducing agent, 60-80 parts of anhydrous ethanol and 20-30 parts of deionized water, and ultrasonically disperse at a frequency of 40kHz for 30-45 minutes to obtain a dispersion. S12. Add 200-250 parts of cement (PO 42.5 ordinary Portland cement), 800-1000 parts of fly ash, 50-80 parts of silica fume, and 10-20 parts of nano calcium carbonate into a V-type mixer in sequence, and dry mix at a speed of 20-30 r / min for 10-15 min to obtain a mixed dry material. S13. The dispersion obtained in step S11 is sprayed evenly onto the mixed dry material in step S12 by spraying, while stirring. After spraying, continue stirring for 15-20 minutes and then place it in an oven to dry for 8-10 hours. The modified gelling material is obtained by passing it through a 200-mesh sieve.
[0011] Preferably, the preparation of modified PVA fiber materials includes the following steps: S21. By weight, add 25-30 parts of PVA fiber to 500-600 parts of modified impregnation solution, stir and react in a water bath at 60-80℃ for 2-4 hours, take it out, wash it 3-4 times, and dry it in an oven at 60-70℃ for 6-8 hours to obtain preliminary modified PVA fiber. S22. Dilute 5-10 parts of VAE emulsion with deionized water to a solid content of 5-10%, add the preliminarily modified PVA fiber obtained in step S21, impregnate for 5-10 minutes, remove, bake at 80-100℃ for 5-10 minutes, and obtain the modified PVA fiber material after natural cooling.
[0012] Preferably, the preparation of the modified impregnation solution includes the following steps: S211. By mass, dissolve 9-12 parts of KH-560 in a mixed solvent of 450-500 parts of anhydrous ethanol and 200-250 parts of deionized water, adjust the pH to 3.5-4.5 with glacial acetic acid, and hydrolyze with magnetic stirring at room temperature for 30-60 minutes. S212. Add 6-10 parts of nano-silica, 3-6 parts of nano-alumina and 6-10 parts of PEG-400 to the hydrolyzed solution, and disperse it ultrasonically at 40kHz for 20-30min to obtain a dispersion. S213. Add 0.3-0.6 parts of dibutyltin dilaurate to the dispersion obtained in step S212, stir at 300-400 r / min for 10-15 min, and let stand for 20-30 min to obtain the modified impregnation solution.
[0013] Preferably, the standard curing temperature in step S4 is 18-22℃ and the relative humidity is ≥95%.
[0014] Preferably, the stirring speed in step S4 is 100-120 r / min.
[0015] Preferably, the drying temperature in step S13 is 50-60°C.
[0016] Preferably, the cleaning reagent used in step S21 is anhydrous ethanol.
[0017] A PVA-ECC composite material that can reduce damage in sub-high temperature environments is prepared by the above-described preparation method.
[0018] Compared with the prior art, the beneficial effects of the present invention are: 1. The modified impregnation solution of this invention delays the thermal degradation of fibers under sub-high temperature conditions, realizes uniform and efficient grafting of nanoparticles on the fiber surface, and the modified impregnation solution is easy to prepare, has good repeatability, and is suitable for industrial production.
[0019] 2. The modified cementitious material of this invention maintains good structural stability in sub-high temperature environments, providing a reliable anchoring foundation for the fibers. The dual modification in the modified PVA fiber material enables the fibers to maintain high tensile strength and interfacial bonding performance in sub-high temperature environments. The synergy of these two aspects improves the heat resistance and interfacial properties of the matrix while achieving comprehensive performance enhancement from the matrix to the fiber. This effectively solves the technical problems of fiber thermal degradation, interfacial deterioration, and tensile property degradation in PVA-ECC in sub-high temperature environments, demonstrating significant technological progress and broad engineering application prospects. Attached Figure Description
[0020] Figure 1 This is a process flow diagram for preparing the PVA-ECC composite material of the present invention, which can reduce damage in sub-high temperature environments; Figure 2 This is a flow chart of the preparation process of the modified cementitious material of the present invention; Figure 3 This is a flow chart of the preparation process of the modified PVA fiber material of this invention; Figure 4 This is a flow chart of the preparation process of the modified impregnation solution of the present invention; Figure 5 This is a SEM image of the modified PVA fiber material obtained at room temperature in Example 1 of the present invention; Figure 6 This is a SEM image of the PVA-ECC composite material obtained in Example 1 of the present invention, which can reduce damage in sub-high temperature environments. Detailed Implementation
[0021] The present invention will now be clearly and completely described in conjunction with embodiments thereof. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0022] Please see Figures 1-6 The present invention provides a technical solution: Example 1 A method for preparing PVA-ECC composite materials that can reduce damage in sub-high temperature environments: Before preparing the PVA-ECC composite material, the modified impregnation solution, modified cementitious material, and modified PVA fiber material are prepared first: The preparation of the modified impregnation solution includes the following steps: S211. Dissolve 9g KH-560 in a mixed solvent of 450g anhydrous ethanol and 200g deionized water, adjust the pH to 3.5 with glacial acetic acid, and hydrolyze with magnetic stirring at room temperature for 30min. S212. Add 6g of nano-silica, 3g of nano-alumina and 6g of PEG-400 to the hydrolyzed solution, and ultrasonically disperse at 40kHz for 20min to obtain a dispersion. S213. Add 0.3g of dibutyltin dilaurate to the dispersion obtained in step S212, stir at 300r / min for 10min, and let stand for 20min to obtain the modified impregnation solution.
[0023] The preparation of modified cementitious materials includes the following steps: S11. Mix 15g of nano silica, 0.5g of polycarboxylate-based high-efficiency water-reducing agent, 60g of anhydrous ethanol and 20g of deionized water, and ultrasonically disperse at a frequency of 40kHz for 30min to obtain a dispersion. S12. Add 200g of P.O 42.5 ordinary Portland cement, 800g of fly ash, 50g of silica fume, and 10g of nano calcium carbonate into a V-type mixer in sequence, and dry mix at a speed of 20r / min for 10min to obtain a mixed dry material; S13. The dispersion obtained in step S11 is sprayed evenly onto the mixed dry material in step S12 by spraying. While spraying, the mixture is stirred. After spraying is completed, the mixture is stirred for 15 minutes and then placed in an oven at 50°C to dry for 8 hours. The modified gelling material is obtained by passing it through a 200-mesh sieve.
[0024] The preparation of modified PVA fiber materials includes the following steps: S21. Add 25g of PVA fiber to 500g of modified impregnation solution, stir and react for 2h under 60℃ water bath conditions, take it out, wash it 3 times with anhydrous ethanol, and dry it in 60℃ oven for 6h to obtain preliminary modified PVA fiber. S22. Dilute 5g of VAE emulsion with deionized water to a solid content of 5%, add the preliminarily modified PVA fiber obtained in step S21 into it, impregnate for 5 minutes, take it out, bake at 80℃ for 5 minutes, and obtain the modified PVA fiber material after natural cooling.
[0025] The preparation of PVA-ECC composite materials that can reduce damage in sub-high temperature environments includes the following steps: S1. Mix 1000g of modified cementitious material and 400g of quartz sand at a speed of 40r / min for 2min to obtain a preliminary mixture; S2. Mix 280g water, 6g high-efficiency water-reducing agent, 1.2g hydroxypropyl methylcellulose, 0.8g triethanolamine and 3g defoamer, and stir at 800 r / min for 3min to obtain a mixed wet material; S3. Add the mixed wet material obtained in step S2 to the preliminary mixture in step S1 while stirring at a speed of 40 r / min. After the addition is complete, stir rapidly at a speed of 100 r / min for 3 minutes to obtain the secondary mixture. S4. Sprinkle 25g of modified PVA fiber evenly into the mixture of the second step in three batches, with an interval of about 30s between each batch. Stir rapidly at 100r / min for 3min and then pour into a standard test mold. Vibrate for 30s, cover with plastic film and let stand for 24h. Then remove the mold and standard cure (temperature is 18℃, relative humidity is 95%) for 24 days to obtain PVA-ECC composite material.
[0026] Example 2 A method for preparing PVA-ECC composite materials that can reduce damage in sub-high temperature environments: Before preparing the PVA-ECC composite material, the modified impregnation solution, modified cementitious material, and modified PVA fiber material are prepared first: The preparation of the modified impregnation solution includes the following steps: S211. Dissolve 12g KH-560 in a mixed solvent of 500g anhydrous ethanol and 250g deionized water, adjust the pH to 4.5 with glacial acetic acid, and hydrolyze with magnetic stirring at room temperature for 60min. S212. Add 10g of nano-silica, 6g of nano-alumina and 10g of PEG-400 to the hydrolyzed solution, and ultrasonically disperse at 40kHz for 30min to obtain a dispersion. S213. Add 0.6 g of dibutyltin dilaurate to the dispersion obtained in step S212, stir at 400 r / min for 15 min, and let stand for 30 min to obtain the modified impregnation solution.
[0027] The preparation of modified cementitious materials includes the following steps: S11. Mix 25g of nano silica, 1g of polycarboxylate-based high-efficiency water-reducing agent, 80g of anhydrous ethanol and 30g of deionized water, and ultrasonically disperse at a frequency of 40kHz for 45min to obtain a dispersion. S12. Add 250g of P.O 42.5 ordinary Portland cement, 1000g of fly ash, 80g of silica fume, and 20g of nano calcium carbonate into a V-type mixer in sequence, and dry mix at a speed of 30r / min for 15min to obtain a mixed dry material; S13. The dispersion obtained in step S11 is sprayed evenly onto the mixed dry material in step S12 by spraying. While spraying, the mixture is stirred. After spraying is completed, the mixture is stirred for 20 minutes and then placed in an oven at 60°C to dry for 10 hours. The modified gelling material is obtained by passing it through a 200-mesh sieve.
[0028] The preparation of modified PVA fiber materials includes the following steps: S21. Add 30g of PVA fiber to 600g of modified impregnation solution, stir and react for 4h under 80℃ water bath conditions, take it out, wash it 4 times with anhydrous ethanol, and dry it in 70℃ oven for 8h to obtain preliminary modified PVA fiber. S22. Dilute 10g of VAE emulsion with deionized water to a solid content of 10%, add the preliminarily modified PVA fiber obtained in step S21 into it, impregnate for 10 minutes, take it out, bake at 100℃ for 10 minutes, and obtain the modified PVA fiber material after natural cooling.
[0029] The preparation of PVA-ECC composite materials that can reduce damage in sub-high temperature environments includes the following steps: S1. Stir 1200g of modified cementitious material and 450g of quartz sand at a speed of 50r / min for 3min to obtain a preliminary mixture; S2. Mix 300g water, 8g high-efficiency water-reducing agent, 1.4g hydroxypropyl methylcellulose, 1.2g triethanolamine and 5g defoamer, and stir at 1000 r / min for 5min to obtain a mixed wet material; S3. Add the mixed wet material obtained in step S2 to the preliminary mixture in step S1 while stirring at a speed of 50 r / min. After the addition is complete, stir rapidly at a speed of 120 r / min for 5 minutes to obtain the secondary mixture. S4. Sprinkle 30g of modified PVA fiber evenly into the mixture of the second step in 4 parts, with an interval of about 40s each time. Stir rapidly at 120r / min for 5min and then pour into a standard test mold. Vibrate for 60s, cover with plastic film and let stand for 48h. Then remove the mold and standard cure (temperature is 22℃, relative humidity is 96%) for 28 days to obtain PVA-ECC composite material.
[0030] Example 3 A method for preparing PVA-ECC composite materials that can reduce damage in sub-high temperature environments: Before preparing the PVA-ECC composite material, the modified impregnation solution, modified cementitious material, and modified PVA fiber material are prepared first: The preparation of the modified impregnation solution includes the following steps: S211. Dissolve 10g KH-560 in a mixed solvent of 470g anhydrous ethanol and 220g deionized water, adjust the pH to 4 with glacial acetic acid, and hydrolyze with magnetic stirring at room temperature for 40min. S212. Add 7g of nano-silica, 4g of nano-alumina and 7g of PEG-400 to the hydrolyzed solution, and ultrasonically disperse at 40kHz for 22min to obtain a dispersion. S213. Add 0.4 g of dibutyltin dilaurate to the dispersion obtained in step S212, stir at 320 r / min for 11 min, and let stand for 22 min to obtain the modified impregnation solution.
[0031] The preparation of modified cementitious materials includes the following steps: S11. Mix 18g of nano silica, 0.6g of polycarboxylate superplasticizer, 70g of anhydrous ethanol and 23g of deionized water, and ultrasonically disperse at a frequency of 40kHz for 35min to obtain a dispersion. S12. Add 220g of P.O 42.5 ordinary Portland cement, 900g of fly ash, 60g of silica fume, and 13g of nano calcium carbonate into a V-type mixer in sequence, and dry mix at a speed of 25r / min for 12min to obtain a mixed dry material; S13. The dispersion obtained in step S11 is sprayed evenly onto the mixed dry material in step S12 by spraying. While spraying, the mixture is stirred. After spraying is completed, the mixture is stirred for 17 minutes and then placed in an oven at 55°C to dry for 9 hours. The modified gelling material is obtained by passing it through a 200-mesh sieve.
[0032] The preparation of modified PVA fiber materials includes the following steps: S21. Add 28g of PVA fiber to 550g of modified impregnation solution, stir and react for 3h under 70℃ water bath conditions, take it out, wash it 3 times with anhydrous ethanol, and dry it in 65℃ oven for 7h to obtain preliminary modified PVA fiber. S22. Dilute 6g of VAE emulsion with deionized water to a solid content of 7%, add the preliminarily modified PVA fiber obtained in step S21 into it, impregnate for 7 minutes, take it out, bake at 90℃ for 7 minutes, and obtain the modified PVA fiber material after natural cooling.
[0033] The preparation of PVA-ECC composite materials that can reduce damage in sub-high temperature environments includes the following steps: S1. Stir 1100g of modified cementitious material and 420g of quartz sand at a speed of 45r / min for 2.5min to obtain a preliminary mixture; S2. Mix 290g water, 7g high-efficiency water-reducing agent, 1.3g hydroxypropyl methylcellulose, 1g triethanolamine and 4g defoamer, and stir at 900r / min for 4min to obtain a mixed wet material; S3. Add the mixed wet material obtained in step S2 to the preliminary mixture in step S1 while stirring at a speed of 45 r / min. After the addition is complete, stir rapidly at a speed of 110 r / min for 4 min to obtain the secondary mixture. S4. 27g of modified PVA fiber was evenly sprinkled into the mixture in the second step in 4 batches, with an interval of about 35s between each batch. After stirring rapidly at 110r / min for 4min, the mixture was poured into a standard mold, vibrated for 40s, covered with plastic film and left to stand for 36h. After demolding, it was cured under standard conditions (temperature of 20℃ and relative humidity of 97%) for 25 days to obtain the PVA-ECC composite material.
[0034] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that no modified impregnation solution was added in this comparative example; the other steps are exactly the same in Comparative Example 1 and Example 1.
[0035] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that no modified PVA fiber material was added in this comparative example; the other steps are exactly the same in Comparative Example 2 and Example 1.
[0036] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the preparation of the modified cementitious material is omitted in this comparative example, and the modified cementitious material is replaced with a mixture of PO 42.5 ordinary Portland cement and fly ash in a mass ratio of 1:4. The remaining steps are exactly the same in Comparative Example 3 and Example 1.
[0037] Performance testing: Appendix Figure 5 This is a SEM image of the modified PVA fiber material obtained in Example 1 of this invention at room temperature. As can be seen from the image, the modified PVA fiber material is generally a regular cylinder with a clear outline and a basically uniform diameter along its length. The surface of the material is generally smooth and dense, with only a small number of tiny particles attached. No obvious cracks, holes, erosion, or localized damage were observed. This indicates that the modified PVA fiber material maintains a relatively complete initial morphology and good structural integrity under room temperature conditions, and its surface has not yet suffered significant thermal damage. The relatively complete and continuous morphology is beneficial to the load-bearing capacity of the modified PVA fiber material and provides a basis for inhibiting crack propagation in ECC through interfacial bonding and bridging.
[0038] Appendix Figure 6 This is a SEM image of the PVA-ECC composite material obtained in Example 1 of the present invention, which can reduce damage in sub-high temperature environments. The modified PVA fiber material exhibits a relatively obvious random distribution in the ECC matrix, with some material encapsulated by the matrix and some material surface adhering to fine particulate hydration products. The overall morphology of the modified PVA fiber material is relatively intact, and no obvious damage is observed on the surface.
[0039] The direct tensile property test method was performed according to JC / T 2461-2018 "Test Method for Mechanical Properties of Highly Ductile Fiber Reinforced Cementitious Composites"; and uniaxial tensile properties of the PVA-ECC composites obtained in Examples 1-3 and Comparative Examples 1-3 were also tested with reference to ISO 13180-1:2026 "Fiber Reinforced Cementitious Composites - Direct Tensile Testing - Part 1: Strain Hardening". Specimens were divided into room temperature specimens and sub-high temperature specimens. Sub-high temperature specimens were subjected to constant temperature treatment at 150℃ for 6h, 9h, and 12h (simulating long-term sub-high temperature service environment) after 28 days of standard curing, and then cooled to room temperature before testing. Dog-bone shaped (dumbbell-shaped) specimens were used, and a universal testing machine equipped with a high-precision extensometer was employed with a loading rate of 0.5mm / min. The final test data are shown in Table 1 below. Table 1. Performance Test Data As shown in Table 1, the PVA-ECC composite materials obtained in Examples 1-3 are superior to the comparative examples in all aspects. This demonstrates that the present invention effectively delays the thermal degradation of the fiber-matrix interface under sub-high temperature conditions through the synergistic effect of modified cementitious materials and modified PVA fibers, maintaining high tensile strength and ductility. This indicates that, under the combined action of various impregnation solutions, modified cementitious materials, and modified PVA fibers, a comprehensive performance improvement from matrix to fiber is achieved. This effectively solves the technical problems of fiber thermal degradation, interface deterioration, and tensile property degradation of PVA-ECC under sub-high temperature conditions, and has significant technological progress and broad engineering application prospects.
[0040] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a PVA-ECC composite material that can reduce damage in sub-high temperature environments, characterized in that, The preparation steps include the following: S1. By weight, mix 1000-1200 parts of modified cementitious material and 400-450 parts of quartz sand at a speed of 40-50 r / min for 2-3 minutes to obtain a preliminary mixture; S2. Mix 280-300 parts water, 6-8 parts high-efficiency water-reducing agent, 1.2-1.4 parts hydroxypropyl methylcellulose, 0.8-1.2 parts triethanolamine, and 3-5 parts defoamer, and stir at 800-1000 r / min for 3-5 min to obtain a mixed wet material; S3. Add the mixed wet material obtained in step S2 to the preliminary mixture in step S1 while stirring at a speed of 40-50 r / min. After the addition is complete, stir rapidly at a speed of 100-120 r / min for 3-5 minutes to obtain the secondary mixture. S4. Sprinkle 25-30 parts of modified PVA fiber evenly into the mixture of the second step in 3-4 times, with an interval of about 30-40 seconds between each time. Stir quickly for 3-5 minutes and then pour into a standard test mold. Vibrate for 30-60 seconds, cover with plastic film and let stand for 24-48 hours. Then remove the mold and cure for 24-28 days to obtain the PVA-ECC composite material. The preparation of the modified cementitious material includes the following steps: S11. By weight, mix 15-25 parts of nano silica, 0.5-1 parts of polycarboxylate-based high-efficiency water-reducing agent, 60-80 parts of anhydrous ethanol and 20-30 parts of deionized water, and ultrasonically disperse at a frequency of 40kHz for 30-45 minutes to obtain a dispersion. S12. Add 200-250 parts of cement, 800-1000 parts of fly ash, 50-80 parts of silica fume, and 10-20 parts of nano-calcium carbonate to a V-type mixer in sequence, and dry mix at a speed of 20-30 r / min for 10-15 min to obtain a mixed dry material; S13. The dispersion obtained in step S11 is sprayed evenly onto the mixed dry material in step S12 by spraying, while stirring. After spraying, continue stirring for 15-20 minutes and then place it in an oven to dry for 8-10 hours. The modified gelling material is obtained by passing it through a 200-mesh sieve.
2. The method for preparing a PVA-ECC composite material that can reduce damage in sub-high temperature environments according to claim 1, characterized in that, The preparation of the modified PVA fiber material includes the following steps: S21. By weight, add 25-30 parts of PVA fiber to 500-600 parts of modified impregnation solution, stir and react in a water bath at 60-80℃ for 2-4 hours, take it out, wash it 3-4 times, and dry it in an oven at 60-70℃ for 6-8 hours to obtain preliminary modified PVA fiber. S22. Dilute 5-10 parts of VAE emulsion with deionized water to a solid content of 5-10%, add the preliminarily modified PVA fiber obtained in step S21, impregnate for 5-10 minutes, remove, bake at 80-100℃ for 5-10 minutes, and obtain the modified PVA fiber material after natural cooling.
3. The method for preparing a PVA-ECC composite material that can reduce damage in sub-high temperature environments according to claim 2, characterized in that, The preparation of the modified impregnation solution includes the following steps: S211. By mass, dissolve 9-12 parts of KH-560 in a mixed solvent of 450-500 parts of anhydrous ethanol and 200-250 parts of deionized water, adjust the pH to 3.5-4.5 with glacial acetic acid, and hydrolyze with magnetic stirring at room temperature for 30-60 minutes. S212. Add 6-10 parts of nano-silica, 3-6 parts of nano-alumina and 6-10 parts of PEG-400 to the hydrolyzed solution, and disperse it ultrasonically at 40kHz for 20-30min to obtain a dispersion. S213. Add 0.3-0.6 parts of dibutyltin dilaurate to the dispersion obtained in step S212, stir at 300-400 r / min for 10-15 min, and let stand for 20-30 min to obtain the modified impregnation solution.
4. The method for preparing a PVA-ECC composite material that can reduce damage in sub-high temperature environments according to claim 1, characterized in that, In step S4, the standard curing temperature is 18-22℃ and the relative humidity is ≥95%.
5. The method for preparing a PVA-ECC composite material that can reduce damage in sub-high temperature environments according to claim 1, characterized in that, The stirring speed in step S4 is 100-120 r / min.
6. The method for preparing a PVA-ECC composite material that can reduce damage in sub-high temperature environments according to claim 1, characterized in that, The drying temperature in step S13 is 50-60℃.
7. The method for preparing a PVA-ECC composite material that can reduce damage in sub-high temperature environments according to claim 2, characterized in that, The cleaning reagent used in step S21 is anhydrous ethanol.
8. A PVA-ECC composite material that can reduce damage in sub-high temperature environments, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.